ANALISIS FINANSIAL DAN SKEMA PEMBIAYAAN PROGRAM PEREMAJAAN, REHABILITASI DAN INTENSIFIKASI CENGKEH / Financial Analysis of Financing Program for Clove Rejuvenation, Rehabilitation and Intensification - Agus Wahyudi, MS (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Clove is used for spice and a raw materialof kretek cigarret industry. In the last five years (2010-2014) the price of clove was relatively higher, hence encourage farmers to improve the crops and increase productivity that are currently relatively low. Programs that can be rolled out are rejuvenation, intensification and rehabilitation in which technological innovation applied. Development funding for the program is possible if the farming isfinancially feasible. This study aimed to analyze the current projected costs, revenue and financial feasibility of clove farming with the application of innovation in line with rejuvenation, intensification and rehabilitation program to improve clove productivity and development funding for the three programs. The financial analysis method was used to analyze input and output values based on market prices. Data of inputs were obtained through a survey of farming in Bogor and Sukabumi in late 2014 and implementation of appropriate innovation for rejuvenation, intensification, and rehabilitation. Data of outputs are projected with basic data obtained from the survey with a corresponding innovation in rejuvenation, intensification, and rehabilitationapplied. The analysis showed that the program of rejuvenation, intensification, and rehabilitation generate revenue streams that were greater than the current cost and can generate sufficient excess (profit) indicated by higher value of NPV, B/C ratio and IRR. Thus the three programs were eligible to apply to external financing through micro-financing. Financing may be granted for investments and working capital, and can be full or partial.Keywords: clove (Syzigium aromaticum), rejuvenation, intensification, rehabilitation, stream of cost, stream of revenue, financial feasibility, and microfinance AbstrakCengkeh merupakan komoditas y ang digunakan untuk rempah dan bahan baku industri rokok kretek. Dalam lima tahun terakhir (2010-2014) harga cengkeh relatif baik sehingga mendorong petani untuk memperbaiki tanaman cengkeh. Hal ini merupakan kesempatan untuk meningkatkan produktivitas tanaman yang saat ini relatif masih rendah. Program yang dapat digulirkan adalah peremajaan, intensifikasi, dan rehabilitasi yang di dalamnya diterapkan inovasi teknologi. Pengembangan pembiayaan untuk program tersebut dimungkinkan jika secara finansial usahatani layak untuk dilaksanakan. Penelitian ini bertujuan untuk menganalisis proyeksi arus biaya, penerimaan dan kelayakan finansial usahatani cengkeh dengan penerapan inovasi dalam rangka peremajaan, rehabilitasi, dan intensifikasi untuk meningkatkan produktivitas cengkeh serta pengembangan skema pembiayaan untuk ketiga program tersebut. Metode yang digunakan adalah analisis finansial yaitu analisis nilai input dan output berdasarkan harga pasar. Data input diperoleh melalui survei usahatani di Bogor dan Sukabumi pada akhir tahun 2014 dan referensi penerapan inovasi intensifikasi, peremajaan, dan rehabilitasi tanaman cengkeh. Data output diproyeksikan dengan data dasar yang diperoleh dari survei dengan kenaikan sesuai inovasi yang diterapkan. Hasil analisis menunjukkan bahwa program peremajaan, rehabilitasi, dan intensifikasi menghasilkan arus penerimaan yang lebih besar daripada arus biaya sehingga dapat menghasilkan NPV, B/C rasio, dan IRR yang memadai. Dengan demikian ketiga program tersebut layak untuk pembiayaan eksternal melalui pembiayaan mikro. Pembiayaan diberikan untuk investasi maupun modal kerja, baik pembiayaan penuh maupun parsial.Kata kunci: cengkeh (Syzigium aromaticum), peremajaan, intensifikasi, rehabilitasi, arus biaya, arus penerimaan, kelayakan finansial, dan pembiayaan mikro.